Indonesia Military Research and Development in Dealing With The Sixth Generation Warfare : The Use of Artificial Intelligence in War Operations - Irvan Arianto Randa Lembang; Romie Oktavianus Bura; R Djoko Andreas Navalino (East Asian Journal of Multidisciplinary Research, 2023)
Technological sophistication brings the world community to be faced with the 6th generation of war, namely war involving the latest technology, artificial intelligence (AI), satellites, and robotics. This indicates that war has gone beyond conventional means, No. longer having to face each other or face to face as happened in the first generation of war. Although in several parts of the world the "classic" war still occurs, it is more sectoral in nature and only in local scale conflicts. The qualitative descriptive research method was chosen because the researcher wanted to get a description of Indonesian military research and development in dealing with the sixth generation warfare: the use of artificial intelligence in war operations. Given the dynamics of the world's rapid technological developments, the Indonesian National Armed Forces (TNI) must be adaptable, one of which is by updating defense equipment that incorporates the concept of artificial intelligence (AI). The use of artificial intelligence by the TNI is a necessity, this is caused by increasingly sophisticated threat patterns, so the use of technology is very relevant to ensuring the security of border areas. Maintaining the integrity of the unitary state of the Republic of Indonesia is a "fixed price," and one of its forms is ensuring the security of the border area.